Fungsi Lutut Pasien Operasi Total Knee Replacement antara Robotik Asisten dan Konvensional: Sistematik Review - Asep Solahudin; Masfuri Masfuri; Liya Arista; Riri Maria (Malahayati Nursing Journal, 2026)
ABSTRACT Patient knee function is closely related to the ability to perform Activities of Daily Living (ADL) due to its connection with mobility. Patients with advanced Osteoarthritis (OA) require Total Knee Replacement (TKR) surgery. Currently, robotic-assisted technology is available for TKR procedures. Nurses play a crucial role in postoperative patient rehabilitation; therefore, the advent of Robotic-Assisted Total Knee Replacement (RA-TKR) technology necessitates nurses' attention in conducting rehabilitation processes related to patient knee function. To determine the knee function of patients undergoing RA-TKR surgery and its impact on nursing practice. A systematic review was conducted using electronic databases such as ClinicalKey, ClinicalKey Nursing, EbscoHost, ProQuest, PubMed, and ScienceDirect. Inclusion and exclusion criteria were established to obtain articles that could address the objectives. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Additionally, Critical Appraisal Tools from the Joanna Briggs Institute (JBI) were utilized. 2.081 articles collected that matched the keywords, 22 articles were analyzed after the PRISMA screening process. Knee function was measured using instruments such as KSS, WOMAC, KOOS, KSKS, KSFS, OKS, and the UCLA Activity Scale. Six articles found that RA-TKR could significantly improve patient knee function compared to Conventional TKR. Nurses, in this regard, should pay special attention to technology adoption and the care strategies required for pre-, intra-, and postoperative TKR patients with robotic assistance. Although most articles indicated no significant difference in knee function between RA-TKR and Conventional TKR patients, the presence of this technology still requires nurses' attention. Future adoption of technology and nursing care strategies for patients undergoing RA-TKR are necessary. Keywords: Knee Function, Robotic Assistance, Total Knee Replacement. ABSTRAK Fungsi lutut pasien erat kaitannya dengan kemampuan untuk memenuhi Activity Daily Living (ADL) sebab berkaitan dengan mobilisasi. Pasien dengan Osteoatritis (OA) lanjut memerlukan operasi Total Knee Replacement (TKR), saat ini hadir teknologi robotik asisten dalam operasi TKR. Perawat memiliki peran dalam rehabilitasi pasien post-operasi, maka hadirnya teknologi Robotik Asisten Total Knee Replacement (RA-TKR) memerlukan perhatian perawat dalam melakukan proses rehabilitasi berkaitan dengan fungsi lutut pasien. Mengetahui fungsi lutut pasien yang menjalani operasi RA-TKR serta dampaknya pada praktik keperawatan. Sistematik review dengan menggunakan databaseelektronik seperti ClinicalKey, ClinicalKey Nursing, EbscoHost, ProQuest, Pubmed, dan Sciencedirect. Kriteria inklusi dan ekslusi ditetapkan agar terkumpul artikel yang dapat menjawab tujuan. Sistematik review ini menggunakan panduan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Selain itu, dilakukan Critical Appraisal Tools menggunakan Joanna Briggs Institute (JBI). 2.081 artikel terkumpul yang sesuai dengan kata kunci, setelah melakukan proses penyaringan dengan PRISMA didapatkan 22 artikel yang dianalisis. Pengukuran fungsi lutut dilakukan dengan menggunakan instrumen seperti KSS, WOMAC, KOOS, KSKS, KSFS, OKS, dan UCLA Activity Scale. Terdapat 6 artikel yang mendapatkan bahwa RA-TKR dapat meningkatkan fungsi lutut pasien secara signifikan dibanding CO-TKR (Conventional-TKR). Perawat dalam hal ini dapat memberi perhatian khusus terkait adopsi teknologi dan strategi asuhan yang diperlukan untuk pre-intra-post operasi pasien TKR dengan Robotik. Meskipun kebanyakan artikel menunjukkan fungsi lutut pasien operasi RA-TKR dan CO-TKR tidak terdapat perbedaan signifikan, hadirnya teknologi tetap perlu perhatian perawat. Adopsi teknologi dan strategi asuhan keperawatan di masa mendatang bagi pasien dengan RA-TKR diperlukan. Kata Kunci: Fungsi Lutut, Robotik Asisten, Total Knee Replacement